Soil aggregation and carbon stabilization in burn and no-burn sugarcane management systems - GUIMARÃES,MARIA DE FÁTIMA (2018)
ABSTRACT Retaining sugarcane straw over the soil after harvesting can improve soil structure and increase soil carbon stabilization, mainly in macroaggregates. We evaluated the carbon content in the aggregate classes in areas under burn and no-burn (adopted for five years) sugarcane management systems, focusing on the superficial layer (0.00-0.20 m). The experiment was carried in an Oxisol and the treatments consisted in burnt sugarcane, manual harvest; burnt sugarcane, mechanized harvest; and no-burn, mechanized harvest. The retention of sugarcane straw on the soil surface is justified by the increase in carbon content and carbon stock in the surface layer (0.00-0.20 m) by restructuring of the soil, even though it cannot match the structure of the soil under native forest. Our results suggest that in no-burn management the carbon not occluded inside aggregates was important to increase carbon stabilization in soil and that more attention should be given to macroaggregates 2.00-8.00 mm present in this management system, that showed higher carbon content and was responsible for increase of the geometric and weight diameter, increasing the erosion resistance in the long term in relation to burn systems.